4.03.004: Jamie Snider and Don Walsh. [1976-1979] - Walsh, Don; Snider, Jamie (1976)
Myself and Jamie Snider needed $800.00 to buy a Custom PA with two EV Speakers. We had to learn an assortment of songs we wouldn't normally play in order to get a gig at The Continental Club on Duckworth St. in St. John's. The owner was going to pay us $800.00 for two nights. In 1977 this was very big money. Of course we did the gig and got our PA. We would put the two big speakers in the back seat of my 1965 Ford Galaxie 500 convertible and go to the gigs. Of course the speakers were so big the roof of the car had to be down so rainy gigs were no fun. What was fun is that I wired the 8-track player in the car to the speakers so that when we were going to gigs we would blast the car stereo.